Validity of the activities-specific balance confidence scale in individuals with chronic obstructive pulmonary disease - Alsubheen, Sanaa A. (2022)
Limited research assessed the validity of the Activities-specific Balance Confidence, ABC) Scale in individuals with chronic obstructive pulmonary disease, COPD) at risk of falls. We report on the scale's construct and criterion validity.